An approximate internal model-based neural control for serial robots with multiple clearance joints. (December 2018) - Yang, Lixin; Zhang, Xianmin
A dynamic model of serial robots with multiple clearance joints is developed. The contact phenomenon in the clearance joint is modeled by a continuous dissipative Hertz contact theory, and the friction force is calculated based on the modified Coulomb's friction law. A neural network method is employed to predict the dynamic response, which avoids the problem in solving the differential algebraic equations. An approximate internal model-based neural control method is proposed to control the undesired effects arising from the joint clearances. The validity of the proposed method is verified by simulation results.